2012
DOI: 10.1111/j.1365-313x.2011.04873.x
|View full text |Cite
|
Sign up to set email alerts
|

H3K36 methylation is critical for brassinosteroid‐regulated plant growth and development in rice

Abstract: SUMMARYMethylation of histone lysine residues plays an essential role in epigenetic regulation of gene expression in eukaryotes. Enzymes involved in establishment of the repressive H3K9 and H3K27 methylation marks have been previously characterized, but the deposition and function of H3K4 and H3K36 methylation remain uncharacterized in rice. Here, we report that rice SDG725 encodes a H3K36 methyltransferase, and its downregulation causes wide-ranging defects, including dwarfism, shortened internodes, erect lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(102 citation statements)
references
References 44 publications
3
96
0
3
Order By: Relevance
“…SDG724 is a class II SET domain protein and is constitutively expressed in various kinds of tissues (see Supplemental Figure 10 online). Members of this class, including SDG4, SDG8, and SDG25 in Arabidopsis and SDG725 in rice, were shown to have H3K36 methylation activities (Zhao et al, 2005;Cartagena et al, 2008;Dong et al, 2008;Cazzonelli et al, 2009b;Grini et al, 2009;Berr et al, 2010a;Ko et al, 2010;Sui et al, 2012). Our study demonstrated that SDG724 is a major factor for H3K36me3 deposition in rice for the following reasons.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…SDG724 is a class II SET domain protein and is constitutively expressed in various kinds of tissues (see Supplemental Figure 10 online). Members of this class, including SDG4, SDG8, and SDG25 in Arabidopsis and SDG725 in rice, were shown to have H3K36 methylation activities (Zhao et al, 2005;Cartagena et al, 2008;Dong et al, 2008;Cazzonelli et al, 2009b;Grini et al, 2009;Berr et al, 2010a;Ko et al, 2010;Sui et al, 2012). Our study demonstrated that SDG724 is a major factor for H3K36me3 deposition in rice for the following reasons.…”
Section: Discussionmentioning
confidence: 73%
“…In the rice genome, at least 35 SET protein coding genes were annotated (Ng et al, 2007), but few have been characterized (Liang et al, 2003;Thakur et al, 2003;B. Ding et al, 2007;Qin et al, 2010;Sui et al, 2012). The plant SET domain-containing (C) Analysis of the global levels of H3K36me1/2/3, H3K4me1/2/3, and H3K9me2 markers in wild-type (WT), lvp1-1, and lvp1-2 plants using H3K methylation tag-specific antibodies.…”
Section: Sdg724 Encodes a Set Domain-containing Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…mutant plants but was upregulated in REF6 overexpression plants, in which the H3K27me3 level at this locus was decreased (Lu et al, 2011). Moreover, H3K36 methylation was shown to regulate BR-related gene expression and plant development in rice (Oryza sativa; Sui et al, 2012). In addition, a proteomic study identified several BR-responsive nucleus-enriched proteins, including nucleosome assembly proteins, HISTONE DEACETY-LASE 2B, and VERNALIZATION INDEPENDENCE3, suggesting that BR-induced gene expression is regulated by chromatin remodeling (Shigeta et al, 2011a(Shigeta et al, , 2011b.…”
Section: Br and Ga Signaling Regulate Histone Modificationmentioning
confidence: 99%
“…Arabidopsis SDG8, also named ASH1 HOMOLOG2, EARLY FLOWERING IN SHORT DAYS, or CAROTENOID CHLOROPLAST REGULATORY1, is the major H3K36 methyltransferase, and its loss-of-function mutants also show pleiotropic defects, including early flowering, reduced organ size, increased shoot branching, altered carotenoid composition, misformed reproductive organs, reduced fertility, and impaired defenses against pathogens (Kim et al, 2005;Zhao et al, 2005;Dong et al, 2008;Xu et al, 2008;Cazzonelli et al, 2009;Grini et al, 2009;Berr et al, 2010a). Interestingly, SDG725, an H3K36 methyltransferase and the closest homolog of SDG8 in rice (Oryza sativa), is involved in promoting brassinosteroid (BR)-related gene expression and rice flowering (Sui et al, 2012(Sui et al, , 2013. SDG724, another H3K36 methyltransferase in rice, also promotes flowering by affecting H3K36 methylation levels at OsMADS50 and RICE FLOWERING LOCUS T1 (RFT1) chromatin (Sun et al, 2012).…”
mentioning
confidence: 99%